Моделирование нестационарного кризиса теплообмена в дисперсно-кольцевых потоках - Ковецкая, М.М.; Скицько, А.И.; Авраменко, А.А.; Басок, Б.И. (Видавничий дім "Академперіодика" НАН України, 2008)
A model of fluid flow and heat transfer in disperse-hooping two-phase streams is developed. The results of investigation of the burnout in a vertical steam-generating channel under unsteady regimes with the falling bulk flow of a heat-carrier are given.